Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/cncr.26471
|View full text |Cite
|
Sign up to set email alerts
|

When parents disclose BRCA1/2 test results: Their communication and perceptions of offspring response

Abstract: Background BRCA1/2 testing is not recommended for children, as risk reduction measures and screening are not generally recommended before 25 years old (YO). Little is known about the prevalence and predictors of parent communication to offspring and how offspring respond to this communication. Methods Semi-structured interviews were conducted with parents who had BRCA1/2 testing and at least one child <25 YO. Logistic regressions were utilized to evaluate associations with communication. Framework analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 52 publications
2
53
1
Order By: Relevance
“…Sample sizes ranged from 10 33 to 505 34 children. Child participant ages ranged from 5 to <25 years 33,34 at the time of testing. The review captured 10 clinical guidance/perspectives articles discussing the psychological impact of genetic testing in children, six (60%) of which were published in the United States.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample sizes ranged from 10 33 to 505 34 children. Child participant ages ranged from 5 to <25 years 33,34 at the time of testing. The review captured 10 clinical guidance/perspectives articles discussing the psychological impact of genetic testing in children, six (60%) of which were published in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that 11% of parents perceived that their children had experienced distress in response to learning about the genetic status of their parents. 33 Another study reported that children's self-report scores for anxiety, depression, and behavioral problems were within the normal range and that most children worried about becoming sick a 'little bit of the time or less' (75%). 25 However, 55% acknowledged worrying 'a fair amount or more' about their risk of developing cancer and 50% reported worrying about a family member's risk.…”
Section: What Is the Psychological Impact On Children Acquiring Genetmentioning
confidence: 99%
See 1 more Smart Citation
“…Although genetic testing and screening for breast cancer are not recommended for children and adolescents, early-life events (e.g., exposures, biologic changes) might modify risks for breast cancer in adulthood (1215) and many health and risk behaviors begin in, or become established during adolescence (1620). The majority of offspring in high-risk families learn of familial and genetic risks for breast cancer during childhood and adolescence (2124). Little is known, however, about adolescent girls’ knowledge, attitudes and beliefs about breast cancer risks.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Many parents discuss genetic and familial risk with their children, and some believe genetic testing should be permitted in adolescence. [12][13][14][15] Furthermore, some adolescent providers would consider testing a daughter of a BRCA1/2 mutation carrier. 16 Additionally, there are new guidelines recommending return of incidental genomic findings (including BRCA1/2 mutations) regardless of age.…”
mentioning
confidence: 99%